Fibre positioning revisited: the use of an off-the-shelf assembly robot for OPTIMOS-EVE - Dalton, G; Whalley, MS; Mounissamy, O; Sawyer, E; Tosh, I; Terrett, D; Lewis, I (2010)
The OPTIMOS-EVE instrument proposed for the E-ELT aims to use the maximum field of view available to the E-ELT in the limit of natural or ground-layer-corrected seeing for high multiplex fibre-fed multi-object spectroscopy in the visible and near-IR. At the bare nasmyth focus of the telescope, this field corresponds to a focal plane 2.3m in diameter, with a plate-scale of ∼3mm/arcsec. The required positioning accuracy that is implied by seeing limited performance at this plate-scale brings the system into the range of performances of commercial off-the-shelf robots that are commonly used in industrial manufacturing processes. The cost-benefits that may be realized through such an approach must be offset against the robot performance, and the ease with which a useful software system can be implemented. We therefore investigate whether the use of such a system is indeed feasible for OPTIMOS-EVE, and the possibilities of extending this approach to other instruments that are currently in the planning stage. © 2010 SPIE.